High resolution 1H and 13C NMR and mass spectral studies of substituted dipyridylpyridazine. Issue 1 (2002) - El-Qisairi El-Qisairi, Arab K. Arab K.
Abstract : Total assignment of the 1 H and 13 C NMR spectra of 3, 6-bis(2'-pyridyl)pyridazine derivatives ( n -dppn) have been recorded at 400 and 100 MHz, respectively. 1 Based on these data, the complete assignment of the 13 C NMR chemical shift values was made by a 13 C 1 H decoupling. The spectra clearly show that the n -dppn ligands exist in the cis–cis conformation at least in solution. Matrix assisted laser desorption ionization (MALDI) and time-of-flight mass spectrometry (TOFMS) are used to record the mass spectra of the n -dppn ligands. α-Cyano-4-hydroxycinnamic acid (CHCA) matrix promoted the molecular ion detection when 180 pmol of n -dppn is introduced into the TOFMS.